Baz Mart's Management Model in Improving the Living Standards of the Poor - Muhammad Erwin Soaduan Pohan; Mustafa Kamal Rokan; Yenni Samri Juliati Nasution (Journal of Economics and Management, 2026)
The BAZ Mart program is a management model designed to improve the lives of people experiencing poverty who cannot manage or develop businesses due to physical disabilities, limited knowledge, or lack of experience. This model enables zakat funds to continue growing and expanding, ensuring their sustainability in meeting the basic needs of beneficiaries. This study aims to determine the improvement in the lives of low-income communities in Pelalawan Regency, Riau, through Baz Mart, a self-service business managed with zakat funds. Buyers are encouraged to shop at Baz Mart through collaboration among the Pelalawan Regency Government, PT Riau Andalan Pulp and Paper (RAPP), and Baznas Pelalawan's outreach program to zakat donors and the wider community under the slogan, "Shopping at Baz Mart means helping to reduce poverty in Pelalawan." This study applies Fred's (2011) strategic management theory, which consists of strategy formulation, implementation, and evaluation. A descriptive qualitative approach was employed using both primary and secondary data. Data were collected through field observations, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. The results demonstrate that the empowerment program has had a positive and significant impact on poverty alleviation in Pelalawan Regency. The findings also confirm that poverty alleviation for mustahik aligns with the developed concept. The most important change is the transformation of mustahik into individuals who are more aware, motivated, and committed to improving their economic condition. Furthermore, this study reveals several empirical facts regarding the implementation of the Baznas Mart (Baz Mart) program in Pelalawan Regency, Riau.